Political institutions as substitute for democracy: a political economy analysis of economic growth - Pereira, Carlos (2009)
This manuscript empirically assesses the effects of political institutions on economic growth. It analyzes how political institutions affect economic growth in different stages of democratization and economic development by means of dynamic panel estimation with interaction terms. The new empirical results obtained show that political institutions work as a substitute for democracy promoting economic growth. In other words, political institutions are important for increasing economic growth, mainly when democracy is not consolidated. Moreover, political institutions are extremely relevant to economic outcomes in periods of transition to democracy and in poor countries with high ethnical fractionalization.